Philosophical Hermeneutics - Gadamer, Hans-Georg 1900-2002; Linge, David E. (Berkeley, CA University of California Press, 1976)
This excellent collection contains 13 essays from Gadamer's Kleine Schriften, dealing with hermeneutical reflection, phenomenology, existential philosophy, and philosophical hermeneutics. Gadamer applies hermeneutical analysis to Heidegger and Husserl's phenomenology, an approach that proves critical and instructive.
Keywords: 20th Century (1901-2000); Philosophy; Hermeneutics